Staying fat for Sarah Byrnes - Crutcher, Chris (Greenwillow Books, 2018)
Class discussions about the nature of man, the existence of God, abortion, organized religion, suicide and other contemporary issues serve as a backdrop for a high-school senior's attempt to answer a friend's dramatic cry for help.